Lived Space, Mental Maps And Advertising - Zich, František (Communication Today, 2025)
This paper deals with the issue of living space and mental maps in relation to advertising. Lived area means the place where a person moves most, like home, streets, means of transportation, workplaces, schools, sports facilities,cultural facilities, etc. The mental map is subjectively mirrored space saved in the consciousness of man. It is a tool of spontaneous orientation in space, the assumption for the decision-making about location of their activities. The methods of exploring mental maps are being mentioned. Research probe results indicate the role of advertising in the lived space and the mental map. In relation to advertising and its place in the lived space a conclusion is being stated that advertising does not belong to the identification characteristics of mental maps, neither in positive – nor in negative sense. Its presence in the lived space is registered by most people; anyway it is accepted as its self-evident integral part, without any significant impact on spatial identification.